“A soul, rubbing the sleep from its eyes in the next world”: Dramaturgical Aspects of Metaphysical Temporality in the Libretti of Alban Berg’s Operas - Vanja Ljubibratić (My University, 2022)
Temporality, as a narrative device, was a central element in Alban Berg’s operas both textually and musically. The systematic form of creating circular structures with palindromes via large-scale retrogrades was meant to turn narrative time back onto itself as an expression of fatalistic negation. This conceptualization held metaphysical implications for Berg that coalesced with his notions of time and space. In his operas, and among other ploys, Berg would appropriate the libretti to textually traverse between the two temporal realms of the empirical world and the metaphysical plane in order to obfuscate the perceptions of reality for his characters, and ultimately put them on paths of predetermined doom through a perpetual repetition of fate, as in the case of Wozzeck. Berg would do this at his own discretion, superseding the authority of the playwrights whose texts he chose to set to music, in order to achieve his desired philosophical and autobiographical outcomes, which were his primary concerns. It will become evident, therefore, that the temporal implications were just as viable textually for Berg as they were musically, but that the metaphysical dimension of those implications were reserved solely for the libretti. Lastly, a comprehensive understanding of these Bergian aesthetics will be brought full circle by making explicit the essential associations of textual metaphysical temporality that Berg shared with and derived from Richard Wagner.